Influence of functional moiety in lupane-type triterpenoids in BACE1 inhibition. (December 2019) - Wagle, Aditi; Seong, Su Hui; Castro, María Julia; Faraoni, María Belén; Murray, Ana Paula; Jung, Hyun Ah; Choi, Jae Sue
Graphical abstract: Highlights: Compound 1 to be a potent competitive BACE1 inhibitor. Tyr198 as an importance residue for the strong affinity of 1‒BACE1 complex along with the other hydrophobic interactions. Importance of 16−OH group in exerting anti-BACE1 activity. Importance of carbonyl at 3 and 16 position of lupane-type triterpenoid over the hydroxyl groups in BACE1 inhibition. Abstract: Lupane-type triterpenoids have shown a potential effect against neurodegenerative disorders. Alzheimer's disease, one of the common neurodegenerative disease, is evident by the accumulation of amyloid-beta (Aβ) plaque in the extracellular regions of the brain. β-site amyloid precursor protein cleaving enzyme 1 (BACE1) is a key enzyme for the Aβ formation via the cleavage of amyloid precursor protein (APP). Therefore, to find the potent BACE1 inhibitors and furthermore to explore the role of the functional group responsible for the strong BACE1 inhibitory activity, we synthesized a series of triterpenoids with lupane skeleton starting from the natural compounds calenduladiol and lupeol . Compound 1 revealed a potent competitive BACE1 inhibitory activity (IC50  = 16.77 ± 1.16 μM; Ki  = 19.38). Furthermore, the molecular docking simulation revealed the importance of Tyr198 residue along with the other hydrophobic interactions for the strong affinity of 1 ‒BACE1 complex. To sum up, our results demonstrated the importance of carbonyl moiety at 3 and 16 position of lupane-type triterpenoid over the hydroxyl group at the same position.